A genome database for a Japanese population of the larvacean Oikopleura dioica. (14th August 2020) - Wang, Kai; Tomura, Ryo; Chen, Wei; Kiyooka, Miho; Ishizaki, Hinako; Aizu, Tomoyuki; Minakuchi, Yohei; Seki, Masahide; Suzuki, Yutaka; Omotezako, Tatsuya; Suyama, Ritsuko; Masunaga, Aki; et al.
Abstract: The larvacean Oikopleura dioica is a planktonic chordate and is a tunicate that belongs to the closest relatives to vertebrates. Its simple and transparent body, invariant embryonic cell lineages, and short life cycle of 5 days make it a promising model organism for the study of developmental biology. The genome browser OikoBase was established in 2013 using Norwegian O. dioica . However, genome information for other populations is not available, even though many researchers have studied local populations. In the present study, we sequenced using Illumina and PacBio RSII technologies the genome of O. dioica from a southwestern Japanese population that was cultured in our laboratory for 3 years. The genome of Japanese O. dioica was assembled into 576 scaffold sequences with a total length and N50 length of 56.6 and 1.5 Mb, respectively. A total of 18, 743 gene models (transcript models) were predicted in the genome assembly, named OSKA2016. In addition, 19, 277 non‐redundant transcripts were assembled using RNA‐seq data. The OSKA2016 has global sequence similarity of only 86.5% when compared with the OikoBase, highlighting the sequence difference between the two far distant O. dioica populations on the globe. The genome assembly, transcript assembly, and transcript models were incorporated into ANISEED (https://www.aniseed.cnrs.fr/ ) for genome browsing and BLAST searches. Mapping of reads obtained from male‐ or female‐specific genome libraries yielded male‐specific scaffolds in the OSKA2016 and revealed that over 2.6 Mb of sequence were included in the male‐specific Y‐region. The genome and transcriptome resources from two distinct populations will be useful datasets for developmental biology, evolutionary biology, and molecular ecology using this model organism. Abstract : Genome of the larvacean, Oikopleura dioica, of the Japanese population was sequenced. The genome and transcriptome assemblies and transcript models were incorporated into ANISEED as a common research resource. Using them, male‐specific Y‐chromosome was characterized.